Customer Perceptions and Competitive Challenges in the Water Sports Industry: A Qualitative Study of Hot Dog Water Sport and Dive Center LLC - Effendy, Royhans; Olga Rudolovna Belova (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2025)
This study analyzes customer perception and competitive challenges in the water sports industry with a qualitative study of Hot Dog Water Sport And Dive Center LLC. The type of research used is descriptive with a qualitative approach. The data collection method uses internal documents and corporate social media monitoring. The analysis used was SWOT and PESTLE analysis. The results of the study with SWOT and PESTLE analysis show that the company's strength lies in safety, service friendliness, and environmental sustainability. However, significant challenges such as inefficient coordination, staff professionalism that needs to be improved, and dependence on the weather require strategic innovation to maintain competitiveness.